2020
DOI: 10.3390/ijerph17218130
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Great East Japan Earthquake on the Employment Status and Mental Health Conditions of Affected Coastal Communities

Abstract: The Great East Japan Earthquake devasted the old community in coastal areas characterized by primary industry. The number of unemployed people increased from 150,000 to 190,000 after the earthquake. All of the adult residents of Shichigahama (18 years old or older), located in the coastal area of the Miyagi prefecture, whose houses were totally or majorly damaged, were recruited for a survey conducted in October 2011. All of the residents who responded with written informed consent were included in this study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…The conversion of household registration could improve the happiness of migrant workers with low educational backgrounds, low income, and contracted land. Another piece of research studied how a threatening event, such as the Great East Japan earthquake that occurred in 2011, impacted the affected population [ 25 ]. This disaster caused a high rate of unemployment in the coastal communities, which in turn negatively impacted their mental health.…”
Section: Resultsmentioning
confidence: 99%
“…The conversion of household registration could improve the happiness of migrant workers with low educational backgrounds, low income, and contracted land. Another piece of research studied how a threatening event, such as the Great East Japan earthquake that occurred in 2011, impacted the affected population [ 25 ]. This disaster caused a high rate of unemployment in the coastal communities, which in turn negatively impacted their mental health.…”
Section: Resultsmentioning
confidence: 99%
“…41,42 (2)-6.Cohort studies in Shichigahama Town, Miyagi Prefecture The Graduate School of Medicine and International Research Institute of Disaster Science (IRIDeS) of Tohoku University conducted 10 years of annual surveys to assess the psychosocial aspects of all residents whose houses were majorly damaged by the disaster in the town of Shichigahama, Miyagi prefecture. [43][44][45][46] The studies suggested associations between psychological distress and physical conditions among residents affected by the disaster. [47][48][49] Like other affected areas, living conditions, 43,50,51 employment status, 46 daily walking habit 45 and social capital 44 were associated with the mental health of the affected community.…”
Section: Clinical Neurosciencesmentioning
confidence: 99%
“…[43][44][45][46] The studies suggested associations between psychological distress and physical conditions among residents affected by the disaster. [47][48][49] Like other affected areas, living conditions, 43,50,51 employment status, 46 daily walking habit 45 and social capital 44 were associated with the mental health of the affected community.…”
Section: Clinical Neurosciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…20 In a longitudinal study in the Netherlands, severe PTSD symptoms persisted in 16.7% of the participants who were affected by an explosion of a firework storage building even after 10 y. 21 After the Great East Japan Earthquake and the collapse of the Fukushima-Daiichi Nuclear Power Plant, the surrounding communities suffered from posttraumatic stress reactions with the prevalence of 14.1-24.9% within 1 y and 15-18.1% within 3 y, [22][23][24][25][26] and this coupled with weakened community responses went on to cause chronic physical diseases, anxiety, and increases in disaster-related suicide in Fukushima in the long-term. 24,27,28 In our previous study of the population affected from the Indian Ocean Tsunami and living in temporary shelter, we found that female gender and causal belief patterns are associated with development of PTSD 6 mo posttsunami.…”
mentioning
confidence: 99%